Environmental and Gender Impacts of Land Tenure Regularization in Africa Pilot Evidence from Rwanda - Ali, Daniel Ayalew (The World Bank, 2011)
Although increased global demand for land has led to renewed interest in African land tenure, few models to address these issues quickly and at the required scale have been identified or evaluated. The case of Rwanda's nation-wide and relatively low-cost land tenure regularization program is thus of great interest. This paper evaluates the short-term impact (some 2.5 years after completion) of the pilots undertaken to fine-tune the approach using a geographic discontinuity design with spatial fixed effects. Three key findings emerge from the analysis. First, the program improved land access for legally married women (about 76 percent of married couples) and prompted better recordation of inheritance rights without gender bias. Second, the analysis finds a very large impact on investment and maintenance of soil conservation measures. This effect was particularly pronounced for female headed households, suggesting that this group had suffered from high levels of tenure insecurity, which the program managed to reduce. Third, land market activity declined, allowing rejection of the hypothesis that the program caused a wave of distress sales or widespread landlessness by vulnerable people. Implications for program design and policy are discussed